Allergic contact dermatitis: a significant environmental and occupational skin disease. (12th March 2021) - Olusegun, Olufunmilayo A.; Martincigh, Bice S.
Abstract: This review article seeks to provide an overview of allergic contact dermatitis (ACD) as a significant environmental and occupational skin disease, the phases of ACD, its causes from the occupational and environmental perspectives, its detection, the effects of ACD with respect to the social, psychological, occupational, and financial perspectives, and its cure and/or prevention. Human skin is very sensitive and as the largest organ in the body, it is highly prone to direct and indirect contact with the substances from its environment. The skin reacts to these substances (xenobiotics) differently depending on the individual's tolerance level or threshold. Allergic contact dermatitis is a significant environmental and occupational skin disease that should not be ignored in our society because it can affect the quality of life of an affected individual. There are multiple causes of ACD, and these causes of ACD have been discussed from two perspectives: environmental and occupational. The effects of ACD can be psychological, social, financial, and occupational. There is need for more public enlightenment on the effects of ACD as well as a precise understanding that it is not a contagious disease so as to significantly reduce the psychological and social effects of ACD on these patients.